Molecular Typing of Dengue Viruses Circulating in Kuching, Sarawak from September 2014 to June 2016 - Bong, Kee Kai (Universiti Malaysia Sarawak (UNIMAS), 2019)
The aim of this study is to investigate the distribution and diversity of dengue viruses circulating in Kuching division of the Sarawak state. Dengue is an acute systemic viral infection which is associated with high mortality and morbidity. In Malaysia, dengue transmission has been a major concern with continuous upsurge of dengue incidences nationally with higher prevalence in urban and peri-urban areas. In this study, collected patient sera were separated into two groups; serologically dengue positive and serologically dengue negative, based on the results of preliminary serological test using commercial SD Bioline dengue kit (NS1 Ag + Ab combo). Pan-flavivirus RT-PCR screenings yielded 86 (26.6 %) positive results out of total 323 samples tested. Meanwhile, 467 serologically dengue negative samples were tested with Real-Time PCR (qPCR), which yielded another 4 (0.9 %) positive results. Overall, a higher rate of virus detection was observed from the group of patient samples with dengue NS1 antigen detected by commercial dengue kit. Age-wise analysis showed that adults of age 21-30 were most infected with dengue compared to other age groups. Besides, dengue isolates were successfully propagated for 61 (49.2 %) samples which were inoculated in C6/36 cell culture. Sequencing results of PCR generated amplicons showed circulation of DENV-1, DENV-2, DENV-3, with co-circulation of at least two serotypes at any one time. Phylogenetic analyses were performed on the basis of viral E gene sequence and C-prM gene junction sequence. Resulted phylogenetic trees revealed distinct clusters of individual dengue serotype with strong bootstrap support. DENV-1 isolate sequences of this study clustered within genotype I, showing high sequence homology to strains from neighboring countries in Southeast Asia. Such phylogenetic relationships indicate frequent exchanges of DENV-1 genotype I strains in the region. DENV-2 isolate sequences grouped within Cosmopolitan genotype. Among these, 11 DENV-2 Cosmopolitan isolates of one sub-lineage were related to Sarawak strains sampled previously. This clustering topology suggests local transmission of the Cosmopolitan strains. Another 10 DENV-2 Cosmopolitan isolates formed a sub-lineage with strains notably from Peninsular Malaysia, Singapore, China and Philippines, suggesting importation from these neighboring localities in Asia. Interestingly, DENV-3 isolate sequences identified in this study clustered within two distinct genotypes; genotype III and genotype I. Among the DENV-3 genotype III isolates, 3 of them were linked to a Singapore strain whereas another 4 formed a sub-lineage with reference strains from Southeast Asia. Similarly, these findings indicate frequent exchanges of dengue strains in the Southeast Asian region. The sole DENV-3 genotype I isolate closely related to a Singapore strains, strongly supports an importation event that is corroborated by the patient’s recent travel history to Singapore. Both phylogenetic analysis approaches based on dengue viral C-prM and E gene sequences resulted in similar clustering topology suggesting that the C-prM sequence would be a useful tool for quick results of molecular typing. In conclusion, this study identified co-circulation of different DENV serotypes and genotypes in Kuching as a result of frequent exchanges of strains among neighboring localities in Southeast Asia.